1998
DOI: 10.1021/ic9709281
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Copper Complexes Displaying N3S Coordination as Models for CuBCenter of Dopamine β-Hydroxylase and Peptidylglycine α-Hydroxylating Monooxygenase

Abstract: We describe the studies of new copper complexes [MeSPY2]CuPF(6), 2, and [MeSPY2]Cu(ClO(4))(2).CH(3)CN, 3, as models for the Cu(B) center of dopamine beta-hydroxylase and peptidylglycine alpha-hydroxylating monooxygenase. The structure of [MeSPY2]Cu(ClO(4))(2).CH(3)CN, 3, has been established by X-ray crystallography. The copper coordination exhibits a square pyramidal geometry where the equatorial plane is occupied by the SCH(3) group and three nitrogen atoms (tertiary amine, one pyridine, and acetonitrile sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 45 publications
3
38
0
Order By: Relevance
“…To understand the possible involvement of the methionine ligand different copper(II) complexes with N3S-type ligand have been prepared in the literature [46][47][48]. A questioning model has been described by Réglier et al [46].…”
Section: Models For Monooxygenases Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand the possible involvement of the methionine ligand different copper(II) complexes with N3S-type ligand have been prepared in the literature [46][47][48]. A questioning model has been described by Réglier et al [46].…”
Section: Models For Monooxygenases Sitesmentioning
confidence: 99%
“…A questioning model has been described by Réglier et al [46]. The complex [MeSPY2Cu](ClO 4 ) 2 AE CH 3 CN (Fig.…”
Section: Models For Monooxygenases Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectroscopic studies have shown that two copper ions are present at the active site of DBH with different coordination spheres in the oxidized and reduced states [22][23][24]. Recently, the water-soluble Cu(II) complex Py 2 SMeCu(II) 8 has emerged as a good model of the N 3 S coordination sphere of the Cu B center of DBH with a reactivity mimicking that of the enzyme [25].…”
Section: Introductionmentioning
confidence: 99%
“…Substantial rate accelerations for hydrolysis, particularly of carboxylic acid esters, have been attained with some of these model Cu(II) and Zn(II) complexes (33)(34)(35)(36). Although Cu complexes, which reasonably mimic the structural and spectroscopic features of the Cu-hydroxylases, have been prepared (37)(38)(39)(40), few possess polyimidazole ligands or have been shown to promote the hydroxylation of relevant substrates (usually stoichiometric hydroxylation of their own ligands is a major problem) (41)(42)(43)(44), and none of these reactions are catalytic.…”
mentioning
confidence: 99%